Efek Hepatoprotektif Ekstrak Buah Merah (Pandanus conoideus Lam.) pada Hati Mencit Jantan Galur Swiss induksi dengan CCl4 - Nugraha, Ari Satia; Hadi, Ninisita Sri; Siwi, Sri Untari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2008)
A research on red fruit (Pandanus conoideus Lam.) has been conducted to determine its hepatoprotective effect.This research was concern on three group of treatments, a blank treatment (water), a standard drug (curcuminecontaining) and red fruit extract treatment group. The liver destruction was induced by CCl 4. The hepatoprotectiveeffect was illustrated by SGOT – SGPT level of activity and percentage of cell destruction obtained from histopatogolicanalysis. Compared to the blank group, which had level of SGOT-SGPT activity as 38224,40  2,92 U/L and SGPT of24128,00  5,22 U/L, the red fruit treatment group showed a lower SGOT – SGPT activity (20112,4  2,68 U/L and18923,0  2,77 U/L, respectively); while the standard drug treatment group showed level of SGOT and SGPT activityas 29732,4  1,85 U/L and 20640,8  3,78 U/L, respectively. The histopatologic evaluation also illustrated similaritythat the red fruit treatment group occupied the lowest percentage of hepatocyte destruction shown as percentageof cell degeneration and cell necrosis of 28,3% and 31,7%, respectively. The standard drug treatment showed78,3% of destruction based on degenerative cell destruction and 88,3% based on cell necrosis. Almost 100% of celldestruction was shown in the blank group. Based on these result, the red fruit extract possessed a liver cellprotection activity against cell destruction caused by CCl4 exposure and even more active than a standard drug.